The A to Z of vitamins, minerals, and supplements - Navarra, Tova (New York : Checkmark Books, 2006)
Provides a look at the nutrients that foods and supplements offer and how they work with the body and offers an A-Z directory on over nine hundred vitamins, minerals, and supplements
Includes bibliographical references (p. 325-330) and index
Keywords: Dietary supplements -- Encyclopedias